British Airways: a case study in social media management - Hanlon, Annmarie (Henry Stewart Talks, 2017)
This case study describes British Airways’ successful approach to its social media presence, demonstrated by the way it handles out of date Twitter accounts and the dramatic difference in appearance and activity of its active Twitter account.